Strategic design thinking innovation in products, services, experiences and beyond - Nixon, Natalie W. (New York Fairchild Books, An imprint of Bloomsbury Publishing Inc., 2016)
"Who can design? For too long, that question has highlighted the supposed division between right-brain dominant "creative types" and left-brain dominant "analytical types." Such a division is not practical for preparing students to become innovative contributors to the complex world of design. Strategic Design guides readers to cultivate hybrid thinking, whether their background is design, finance, or any discipline in between. This book is an introduction to an integrative approach using the lens of design thinking as a way to see the world. The focus is on process instead of solution, and on connecting disparate ideas instead of getting bogged down by silos of specialization. Through this book, students will be introduced to design management, strategic design, service design, and experience design"-- Provided by publisher.
Part I: The Why -- Chapter 1: Theoretical Context / Alison Rieple -- Chapter 2: Semiotics / Joseph Hancock -- Chapter 3: Rhetoric / Valerie Jacobs -- Part II: The How -- Chapter 4: Methods / Steve Wilcox -- Chapter 5: Models & Frameworks / Michelle Miller -- Chapter 6: Tools / Cindy Tripp -- Part III: The What -- Chapter 7: Integrative Spaces / Natalie Nixon -- Chapter 8: Design Thinking in Action, Design Thinking Everywhere / Natalie Nixon.
Includes bibliographical references and index.
Keywords: Creative ability in business; Creative thinking; Design; Organizational change